Optimization of Grouper Nursery Rearing Techniques to Improve Production Yields at CV. Bali Akkua Marine - Jefri Putri Nugraha; Putri Nurhanida Rizky (Universitas Islam Lamongan, 2026)
The optimization of nursery rearing techniques plays a crucial role in improving the survival rate and growth performance of cantang grouper (Epinephelinae). This study evaluates the effectiveness of a two-stage nursery rearing system at CV. Bali Akkua Marine, Bali, in enhancing production efficiency and economic feasibility. The results showed a consistently high survival rate of 95% across both phases. The reduction in stocking density in the second phase minimized stress and improved fish growth, while optimized water quality management, including filtration and flow-through systems, maintained stable environmental conditions. In addition, tailored feeding strategies incorporating vitamin C, probiotics, and Enrofloxacin 2S improved feed efficiency (FCR 1.3) and fish health. Economic analysis indicated that the system is highly feasible, with an R/C ratio of 3.48 and a break-even point far below actual production levels, demonstrating a high margin of safety. These findings highlight that the integration of optimized technical practices and efficient resource utilization can significantly enhance both production performance and economic sustainability in grouper nursery operations.